CITRA DIRI SEBAGAI STIMULUS PENCIPTAAN KARYA SENI LUKIS - Mutiara Daulay; Miswar Miswar; Yunis Muler (Educraf : Journal Of Craft Education, Craft Design And Creative Industries, 2022)
Self-image is an individual's knowledge of self related to mental images, personality, appearance, and abilities. The self-image that is built from time to time can be very positive or negative, the determinant of this can be seen from the stages of psychosocial development theory, the turbulent phase for the author from the adolescent stage to early adulthood. Based on the author's experience of the self that developed during the maturation process when searching for identity and living in a new environment, it cause to negative speculations about self. This self-perception becomes a stimulus for writers in creating works of art. The presence of this work is a form of self-reflection to become a better individual. The form of artwork that is realized is representational artwork using deformation in the form of idealization with mixed media on canvas using plaque and aquarel techniques. The method of creation carried out at the preparation stage is selecting ideas, observing objects, and producing reference images, proceeding to the design stage, this stage making visual strategies, alternative sketches, and selecting sketches, then at the embodiment stage the preparation of tools and materials and transfer of sketches onto canvas as a painting medium, cultivating the work to completion and proceeding to the presentation stage, after all the stages are carried out then an exhibition is held. The project of this work has been realized into five works of art, with the titles “Anxiety”, “Ego”, “Field of Mind”, “Reparation”, “Reflective Decision”.